Punching the air ebook - Zoboi, Ibi (2020)
New York Times and USA Today bestseller * Boston Globe-Horn Book Honor * Walter Award Winner * Goodreads Finalist for Best Teen Book of the Year * Time Magazine Best Book of the Year * Publishers Weekly Best Book of the Year * Shelf Awareness Best Book of the Year * School Library Journal Best Book of the Year * Kirkus Best Book of the Year * New York Public Library Best Book of the Year From award-winning, bestselling author Ibi Zoboi and prison reform activist Yusef Salaam of the Exonerated Five comes a powerful YA novel in verse about a boy who is wrongfully incarcerated. A must-read for fans of Jason Reynolds, Walter Dean Myers, and Elizabeth Acevedo. The story that I thought was my life didn't start on the day I was born Amal Shahid has always been an artist and a poet. But even in a diverse art school, because of a biased system he's seen as disruptive and unmotivated. Then, one fateful night, an altercation in a gentrifying neighborhood escalates into tragedy. "Boys just being boys" turns out to be true only when those boys are white. The story that I think will be my life starts today Suddenly, at just sixteen years old, Amal is convicted of a crime he didn't commit and sent to prison. Despair and rage almost sink him until he turns to the refuge of his words, his art. This never should have been his story. But can he change it? With spellbinding lyricism, award-winning author Ibi Zoboi and prison reform activist Yusef Salaam tell a moving and deeply profound story about how one boy is able to maintain his humanity and fight for the truth in a system designed to strip him of both.